2020
DOI: 10.15288/jsad.2020.81.725
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Alcohol Consumption Among College Students Due to COVID-19: Effects of Campus Closure and Residential Change

Abstract: It is well established that college students increase their drinking when they leave home. This study examined changes in drinking as a result of campus closure due to coronavirus disease 2019 (COVID-19), focusing on the influence of living situation. Method: A sample of 312 college students (mean age = 21.2 years; 62% female; 67% White) responded to an online survey regarding their drinking behavior before and after university closures because of COVID-19. Those participants who lived with peers pre-closure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
112
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 26 publications
18
112
1
2
Order By: Relevance
“…Other interesting examples may be the decrease of alcohol consumption in college students, after the campus closure, the main explanation being that they got back home, to live with their families, with less social events and binge drinking [ 46 , 47 ].…”
Section: Short- and Long-term Alcohol Consumption During Covid- 19mentioning
confidence: 99%
“…Other interesting examples may be the decrease of alcohol consumption in college students, after the campus closure, the main explanation being that they got back home, to live with their families, with less social events and binge drinking [ 46 , 47 ].…”
Section: Short- and Long-term Alcohol Consumption During Covid- 19mentioning
confidence: 99%
“…temporary closing of restaurants, fitness centers, bars and pubs). Consistently, evidence suggests that during the COVID-19 pandemic, university students’ food consumption habits have become healthier (Duong et al, 2020 ), physical activity increased (Romero-Blanco et al, 2020 ), and alcohol use decreased (White, Stevens, Hayes, & Jackson, 2020 ). Also, our sample may eventually exhibit worsened health behaviors as a result of leaving the parental home, but these changes may not happen early in the first semester (Small et al, 2013 ).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, drinking frequency was higher when drinking with parents versus alone or with friends. Our group recently demonstrated that moving from living with peers to parents following COVID‐related campus closure was associated with reductions in quantity and frequency of consumption (White et al, 2020a,b). The present work builds on this earlier study by examining additional indices of drinking and providing a much more comprehensive examination of context, both physical and social, as well as examining reasons for changes in drinking.…”
Section: Understanding Covid‐19‐related Changes In Alcohol Involvementmentioning
confidence: 99%